2011
DOI: 10.1111/j.1467-9671.2010.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Urban Street Characteristics on Pedestrian Heat Comfort Levels in Philadelphia

Abstract: This article describes relationships between selected physical characteristics of urban streets and pedestrianlevel heat. It also identifies conditions that are particularly vulnerable to the summer heat. Field measurements of ambient temperatures 1 m above the ground were collected over sidewalks, green spaces, and parking lots in high density commercial and residential areas. Panel autoregression (PAR) analysis was then used to assess significant contributors, and prediction equations were developed. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Trees contribute to population health by: improving in air quality by exchanging and absorbing various gases and airborne pollutants (e.g. particulate matter), which can have implications for respiratory health, including lower rates of asthma (Lovasi et al, 2008; Nowak et al, 2006); providing shade and cooling ambient air temperature by diverting solar radiation and evapotranspiration, which in turn, helps minimize exposure to harmful ultraviolet radiation from the sun and reduce heat-related stress and deaths (Georgi and Zafiriadis, 2006; Basu and Samet, 2002; Heisler and Grant, 2000; Brown University, 2010; Oka, 2011); reducing stress and promoting more relaxed physiological states (Kaplan and Kaplan, 2003; Velarde et al, 2007); making open spaces more pleasant, encouraging physical activity (Bedimo-Rung, 2005; Sullivan et al, 2004; Corti et al, 1996); and mitigating the effects of noise (Fang and Ling, 2005; Gidlöf-Gunnarsson, 2007). Additionally, trees are associated with the reduced risk of poor pregnancy outcomes, i.e.…”
Section: Trees Population Health and Community Wellbeing: Benefits Omentioning
confidence: 99%
“…Trees contribute to population health by: improving in air quality by exchanging and absorbing various gases and airborne pollutants (e.g. particulate matter), which can have implications for respiratory health, including lower rates of asthma (Lovasi et al, 2008; Nowak et al, 2006); providing shade and cooling ambient air temperature by diverting solar radiation and evapotranspiration, which in turn, helps minimize exposure to harmful ultraviolet radiation from the sun and reduce heat-related stress and deaths (Georgi and Zafiriadis, 2006; Basu and Samet, 2002; Heisler and Grant, 2000; Brown University, 2010; Oka, 2011); reducing stress and promoting more relaxed physiological states (Kaplan and Kaplan, 2003; Velarde et al, 2007); making open spaces more pleasant, encouraging physical activity (Bedimo-Rung, 2005; Sullivan et al, 2004; Corti et al, 1996); and mitigating the effects of noise (Fang and Ling, 2005; Gidlöf-Gunnarsson, 2007). Additionally, trees are associated with the reduced risk of poor pregnancy outcomes, i.e.…”
Section: Trees Population Health and Community Wellbeing: Benefits Omentioning
confidence: 99%
“…In environmental health research, simpler heat index algorithms are typical (e.g., Barnett et al 2010; Halonen et al 2011a; Smoyer-Tomic and Rainham 2001; Vaneckova et al 2011; Zanobetti and Schwartz 2005). More complex algorithms are more common in climatology studies (e.g., Fischer and Schär 2010; Oka 2011), although some environmental health studies have used these more complex algorithms as well (e.g., Fletcher et al 2012; Lajinian et al 1997; Tam et al 2008). The NWS uses its own complex algorithm for forecasts and heat warnings (Figure 3) and has created a website that calculates heat index using this algorithm, although only for one heat index value at a time (NWS 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Harlan et al (2006) found that neighborhoods in Phoenix with high building density, less vegetation and open space experienced increased temperatures. Oka (2011) suggested that human heat comfort levels in Philadelphia were a function of urban street characteristics, surface materials and time of a day. Finally, Houet and Pigeon (2011) used an automated method to classify and map Urban Climate Zones and compare the temperature data measured in the field to satellite-derived surface temperature in these zones.…”
Section: Introductionmentioning
confidence: 99%